Rapidly Improving High Light and High Temperature Tolerances of Cyanobacterial Cell Factories Through the Convenient Introduction of an AtpA-C252F Mutation - Zhang, Shanshan; Zheng, Sini; Sun, Jiahui; Zeng, Xuexia; Duan, Yangkai; Luan, Guodong; Lu, Xuefeng (Frontiers in Microbiology, 2021)
Photosynthetic biomanufacturing is a promising route for green production of biofuels and biochemicals utilizing carbon dioxide and solar energy. Cyanobacteria are important microbial platforms for constructing photosynthetic cell factories. Towards scaled outdoor cultivations in future, high light and high temperature tolerances of cyanobacteria chassis strains and cell factories would be determinant properties to be optimized. We proposed a convenient strategy for rapidly improving high light and high temperature tolerances of an important cyanobacteria chassis Synechococcus elongatus PCC 7942 and the derived cell factories. Through introduction and isolation of an AtpA-C252F mutation, PCC 7942 mutants with improved high light and high temperature tolerances could be obtained in only 4 days with an antibiotics free mode. Adopting this strategy, cellular robustness and sucrose synthesizing capacities of a PCC 7942 cell factory were successfully improved.